Pengaruh Strategi Konseling Berimbang Terhadap Pemilihan Kontrasepsi Modern di Kota Padang - Rafika Oktova; Henni Fitria; Yulizawati Yulizawati; Resty Sri Handayani (Universitas Pahlawan Tuanku Tambusai, 2025)
One of the additional family planning counseling methods in Indonesia that has been adapted since August 2016 until now to improve postpartum family planning counseling services is the balanced counseling strategy (BCS). The purpose of this study was to determine the effect of BCS on the behavior of using modern contraception. This quantitative research type was quasi-experimental with a non-randomized pretest-posttest with a control group design. Data collection was conducted from August to November 2023. The study sample was 20 postpartum women in each intervention and control group. The sampling technique was quota sampling. The research instrument was a structured questionnaire to measure the knowledge, attitudes, and decisions before and after the intervention. Data analysis used the Wilcoxon test (p<0.05). The intervention group had an average increase in knowledge, attitudes, and decisions in choosing family planning: 1.15, 0.90, 0.65. Control group, the average increase in knowledge, attitudes, and decisions in choosing family planning was 1.10, 0.85, and 0.55. The results of the Wilcoxon test (p=0.001). N-gain score for knowledge (0.785), attitude (0.818), and decisions (0.650). Counseling has a positive impact on knowledge, attitudes, and decisions regarding modern contraception selection, making the BCS method highly effective for postpartum family planning counseling.